Emerging health issues of cyanobacterial blooms - Maura Manganelli; Simona Scardala; Mara Stefanelli; Francesca Palazzo; Enzo Funari; Susanna Vichi; Franca Maria Buratti; Emanuela Testai (Istituto Superiore di Sanità, 2012)
This paper describes emerging issue related to cyanobacterial dynamics and toxicity and human health risks. Data show an increasing cyanobacteria expansion and dominance in many environments. However there are still few information on the toxic species fitness, or on the effects of specific drivers on toxin production. Open research fields are related to new exposure scenario (cyanotoxins in water used for haemodialysis and in food supplements); to new patterns of co-exposure between cyanotoxins and algal toxins and/or anthropogenic chemicals; to dynamics affecting toxicity and production of different cyanotoxin variants under environmental stress; to the accumulation of cyanotoxins in the food web. In addition, many data gaps exist in the characterization of the toxicological profiles, especially about long term effects.